1999
DOI: 10.1021/jp990803c
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Disordered Hydrogen Bonding Arrangement in Solid Triphenylmethanol

Abstract: In the crystal structure of triphenylmethanol (Ph3COH), the molecules form hydrogen-bonded tetramers, with the oxygen atoms positioned approximately at the corners of a tetrahedron. In the average crystal structure, three of the Ph3COH molecules (denoted as “basal”) in the tetramer are related to each other by a 3-fold rotation axis and the fourth molecule (denoted as “apical”) lies on this axis. Previously, the dynamic properties of the hydrogen-bonding arrangement have been probed through solid-state 2H NMR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In the temperature range studied, the rate of the 1801-jump motion of the phenyl rings in TPM is several orders of magnitude slower than the dynamics of the hydrogen bonding in this material [3]. Thus, the hydrogen bond dynamics is already in the rapid motion regime (timescale shorter than ca.…”
Section: Article In Pressmentioning
confidence: 89%
See 1 more Smart Citation
“…In the temperature range studied, the rate of the 1801-jump motion of the phenyl rings in TPM is several orders of magnitude slower than the dynamics of the hydrogen bonding in this material [3]. Thus, the hydrogen bond dynamics is already in the rapid motion regime (timescale shorter than ca.…”
Section: Article In Pressmentioning
confidence: 89%
“…To assess the dynamic properties of the hydrogen bonding arrangement in TPM, solid-state 2 H NMR studies were carried out [3] on the selectively deuterated material (C 6 H 5 ) 3 COD; the results confirmed that the disorder in the hydrogen bonding arrangement is indeed dynamic. In the dynamic model established from these studies, the deuteron of the apical molecule undergoes a 3-site 1201-jump motion by rotation about the C-O bond (with equal populations of the three sites), whereas the deuteron of each basal molecule undergoes a 2-site 1201-jump motion by rotation about the C-O bond.…”
mentioning
confidence: 87%
“…have been characterized to date. The supramolecular structures of pure Ph 3 COH and Ph 3 SiOH are entirely different: Ph 3 COH forms tetrahedral aggregates (Ph 3 COH) 4 , containing mobile hydroxyl H atoms (Ferguson et al, 1992;Aliev et al, 1998;Serrano-Gonza  lez et al, 1999), while Ph 3 SiOH forms cyclic aggregates (Ph 3 SiOH) 4 , containing fully ordered hydroxyl H atoms (Bowes et al, 2002). On the other hand, the adducts formed by dimethylsulfoxide with Ph 3 COH (Weber et al, 1989) and Ph 3 SiOH (Bowes et al, 2002) are isostructural.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies included a detailed analysis of the disordered hydrogen‐bonding arrangement in triphenylmethanol using single‐crystal neutron diffraction and an investigation of the contrasting hydrogen‐bond dynamics in the silicon analogue triphenylsilanol using solid‐state 2 H NMR . A theoretical study of the pathways for hydrogen‐bond switching in a geometrically similar model system, comprising a tetrahedral hydrogen‐bonded arrangement of methanol molecules, has also been reported …”
Section: Dynamic Properties Of Crystalline Solidsmentioning
confidence: 99%